САМОИДЕНТИФИКАЦИЯ ЛИЧНОСТИ И НЕКОТОРЫЕ ЦЕННОСТНЫЕ ПРЕДПОЧТЕНИЯ В КАРТИНЕ МИРА ЖИТЕЛЕЙ КАЛМЫКИИ - Dordzhi Adyanovich Sharmandzhiev (Oriental Studies, 2018)
In the article some value preferences of population of the Republic of Kalmykia are considered. The term self-identification of a person is used as a paradigm of value picture of the world of the man.